Uma releitura feminista da teoria da justiça: debates entre Rawls e Okin - Stefany Vaz Despinoy (2020)
The present study starts from the clash between John Rawls' theory of justice and the criticisms that were made by feminist authors, especially Susan Moller Okin, in the work “Justice, Gender and the Family” (OKIN, 1989). The considerations of Okin, who is liberal as well as Rawls, are not intended to replace or destroy the author's theory of justice, but only to make it more inclusive for women. The aspects of “A Theory of Justice” (RAWLS, 1999) criticized by Okin were answered by the author in "Justice as equity: a reformulation" (2003). Despite this, Rawls did not satisfactorily solve the problems mentioned. However, we believe in the potential of Rawlsian theory itself, with the necessary adaptations, to include women. Rethinking the theory of justice provides greater chances that women are “free and equal” people, who participate in social cooperation more equitably (mitigating the effects of the sexual division of labor) and guaranteeing them opportunities to choose the way (including professional occupation), as well as promoting better distribution of primary goods. The separation between public and private sphere is relative and should not serve to justify the state's inertia in promoting equality in the private sphere. There are different feminist approaches on how to combat gender-based injustices (sameness, difference and domination). All of them can be valid to promote equality. With feminist notes, Rawlsian concepts can be rethought in order to become closer to the ideal of promoting justice as equity for all people, including women.